ANALISIS PERSEPSI KULIAH KEWIRAUSAHAAN DALAM MEMBENTUK MINAT BERWIRAUSAHA MAHASISWA - Tapi Rumondang Siregar; Ramdhansyah Ramdhansyah; Esa Setiana (Fakultas Ekonomi Universitas Negeri Medan, 2024)
This study aims to examine the effect of perceptions of entrepreneurship lectures on students' entrepreneurial intention in the Department of Entrepreneurship, Faculty of Economics, Universitas Negeri Medan. This study is important because the Department of Entrepreneurship is a department that has the vision of creating new entrepreneurs among undergraduates. The purpose of this department to form graduates who are not job seeking oriented but focus on entrepreneurship and creating jobs. Given that this department is just operating in the 2020-2021 academic year and does not yet have alumni, it is necessary to conduct research on the effectiveness of lectures in the department of entrreprenership as measured by students' entrepreneurial intention. The survey was conducted using a Likert scale questionnaire. The collected data were analysed using Structural Equation Modelling (SEM) using Smart PLS. The results found that the perception of entrepreneurship lectures has a positive effect on students' entrepreneurial intention. The results of this study emphasise the importance of providing good perceptions of entrepreneurship lectures to students to develop their entrepreneurial intention.